Fabrication of Superhydrophobic Film on the Surface of Indonesian Bamboo Timber by TiO2 Deposition and Using Octadecyltrichlorosilane as a Surface Modifier Agent - Diana Vanda Wellia; Wulandari Wulandari; Arifah Mustaqimah; Nurul Pratiwi; Yulia Eka Putri (Indonesian Journal of Chemistry, 2020)
The tropical bamboo has been widely used in modern society as a potential material for various applications. It is well known that bamboo has low durability due to its hydrophilic properties. To overcome this problem, the superhydrophobic surface on Indonesian bamboo timber had been successfully fabricated via hydrothermal deposition of an anatase TiO2 and solution immersion of octadecyltrichlorosilane (ODTS), which exhibited a maximum water contact angle (WCA) of 155°. The as-fabricated superhydrophobic bamboo timber not only showed high mechanical resistance against the abrasion of SiC sandpaper but had also been proven to possess high chemical stability after immersion in acidic and basic aqueous solutions. Moreover, the superhydrophobic bamboo timber also demonstrated excellent self-cleaning and flame-resistance properties, in comparison to pure bamboo timber. It is believed that the strategy offered in this study can increase the utilization of bamboo timber for various purposes, especially as a self-cleaning material.